A comparison of the effect of the application of kinesiology taping to the use of upper limb compression products in the second phase of treating lymphoedema in patients after mastectomy - Opuchlik, Anna M.; Biskup, Małgorzata; Solakiewicz, Marcin; Kamińska-Gwóźdź, Ewelina; Ridan, Tomasz; Włoch, Anna; Lipińska, Anna Maria (Medical Studies/Studia Medyczne, 2014)
Aim of the research : The aim of this study was to answer the question of whether wearing compression products on the upper limb in the second phase of complex decongestive therapy (CDT) can be replaced with lymphatic application of kinesiology taping. The importance of antiedematous prophylaxis and the impact of complementary treatment on the results of physiotherapeutic management were assessed. Material and methods: Retrospective analysis was applied in 80 women after mastectomy treated for lymphoedema in the Holycross Cancer Centre in Kielce. The method CDT was applied in all the patients in phase I. In phase II, 50 (62%) women used compression sleeves in everyday life, and lymphatic applications of Kinesiology Taping (KT) were introduced in 30 (38%) patients. The research included the following: interview, linear measurement of the upper limb circumferences, palpation of tissues, and assessment of pain; statistical analysis in terms of these parameters was also performed. Results : Application of antiedematous prophylaxis was confirmed by 65% of the women, and complementary treatment was introduced in 75% of the patients from both groups. After phase I of the CDT a significant reduction in the circumferences of the limb in patients from both groups was demonstrated. Comparable results were observed after phase II, but in the second group the circumferences underwent a slight increase. After phases I and II of the therapy there was a beneficial change in the consistency, from hard into soft in both groups. Conclusions : The applied antiedematous prophylaxis was not essential in the course of the treatment. Introduction of radiotherapy had a significant impact on the state of the oedema. Application of physiotherapy resulted in an improvement in the oedema parameters in all the patients after phase I of the therapy. The results were maintained in the phase II in the women who used compression sleeves. Applications of KT did not provide an improvement of the state of the limb circumferences in phase II, but they affected the maintenance of the right oedema consistency and caused a reduction in pain.